Down the Garden Path: Divinity, Space, and Poetics in the Carmina Priapea. - Watson, J. L. (Classical Philology, 2025)
This article argues that the Priapus of the Carmina Priapea is trapped—spatially and poetologically—by the domain over which he presides: lewd obscenity. I show how the CP 's garden becomes the only space in which Priapus could live while being the obscene creature that he is, which creates a series of poetic consequences that are devastating for the garden god. In particular, I examine Priapus' spatial articulation vis-à-vis other divine figures and the walls of his garden to show how obscene poetry is the undoing of the obscene god.